Simulation numerique par nne methode d' elements finis optimale des equations de N avier-Stokes en formulation - Ghadi, Fatteh Allah; Ruas, Vitoriano; Wakrim, Mohamed (European Journal of Computational Mechanics, 2000)
This paper present numerical results for the Navier-Stokes problem in terms of the stream-function and the vorticicty, obtained by our mixte approach [GHA 95] based on the decomposition of the vorticity function, in the case k = l,for the problem of the driven cavity and the backstep problem. In order to prove the performance of this method a comparision with the existing results is done.